Development of a Simple Chromatographic Method for the Determination of Piracetam in Human Plasma and Its Pharmacokinetic Evaluation - Barkat, K.; Ahmad, M.; Minhas, M. U.; Malik, M. Z.; Sohail, M. (Drug Research, 2014)
The objective of study was to develop an accurate and reproducible HPLC method for determination of piracetam in human plasma and to evaluate pharmacokinetic parameters of 800 mg piracetam.A simple, rapid, accurate, precise and sensitive high pressure liquid chromatography method has been developed and subsequently validated for determination of piracetam. This study represents the results of a randomized, single-dose and single-period in 18 healthy male volunteers to assess pharmacokinetic parameters of 800 mg piracetam tablets. Various pharmacokinetic parameters were determined from plasma for piracetam and found to be in good agreement with previous reported values. The data was analyzed by using Kinetica® version 4.4 according to non-compartment model of pharmacokinetic analysis and after comparison with previous studies, no significant differences were found in present study of tested product.The major pharmacokinetic parameters for piracetam were as follows: t1/2 was (4.40±0.179) h; Tmax value was (2.33±0.105) h; Cmax was (14.53±0.282) µg/mL; the AUC0–∞ was (59.19±4.402) µg · h/mL. AUMC0–∞ was (367.23±38.96) µg. (h)2/mL; Ke was (0.16±0.006) h; MRT was (5.80±0.227) h; Vd was (96.36±8.917 L).A rapid, accurate and precise high pressure liquid chromatography method was developed and validated before the study. It is concluded that this method is very useful for the analysis of pharmacokinetic parameters, in human plasma and assured the safety and efficacy of piracetam, can be effectively used in medical practice.
Keywords: pharmacokinetic; piracetam; HPLC; validation